Historical documentation of the UPV main building - Madrid, Randy M. (2008)
The study is basically a documentation of the history of the University of the Philippines Visayas Main Building from the time it was envisioned in 1908, conceptualized in 1929, constructed in 1933, finished in 1936, became the city hall from 1937 to 1947, and turned over as UPV property from 1947 to the present.
Library, archival research and field interviews were employed in data-gathering. The first two processes were devoted to the reconstruction of the history of the building by consulting books, reference materials, and archival records from the libraries and archives of Iloilo and Manila. Field interviews were also conducted in Iloilo City, Miagao, and in other areas where key informants lived. Respondents include past city government officials and employees, University administrators, faculty, and staff, UPV Alumni, relatives of builders and planners of the building who were identified through referrals from government and university officials, UPV alumni director, and other agencies and institutions that were knowledgeable of the topic. Data gathered from interviews were verified and interpreted through the three-person test and field observation.
Keywords: Historic buildings; University of the Philippines (Visayas)